A REVIEW OF ADAPTIVE VIBRATION ABSORBERS FOR VIBRATION ISOLATION OF BEAMS - Hemant D. Supekar; S. H. Kadhane (International Journal of Innovations in Engineering Research and Technology, 2021)
The vibration absorbers are frequently used to control and to minimize excess vibration in structural systems. To reduce the vibration of the main system or machine, the frequency of absorber should be equal to the excitation frequency. This result in Subcomponent of total structure adding large input impedance to the primary structure, thus ‘absorbing’ the internal energy transferred to form primary structure. The vibration absorbers are frequently used to control and to minimize excess vibration in structural systems. The Dynamic vibration absorbers are used to reduce the undesirable vibrations in many applications such as electrical transmission lines, pumps, machine tools, gas turbines, engine, bridges, structures etc. To reduce the vibration of the main system or machine, the frequency of absorber should be equal to the excitation frequency. This result in subcomponent of total structure adding large input impedance to the primary structure, thus ‘absorbing’ the internal energy transferred to form primary structure. The aim of this review work is to study various types of dynamic vibration absorber with variable stiffness mechanism for tuning and to study design of the tunable vibration absorber for vibration control of primary system (beam structure) using finite element method through an Ansys. Its stiffness can be varied to adapt the changes in excitation frequencies. Traditional means of vibration control have involved the use of passive and active methods. This study involves the design and implementation of control system to make absorber tunable by incorporating the use of ball screw for varying the stiffness of secondary system. The objective of this review work is to introduce methods of vibration control and describe practical methods for their application. Several scenarios and case studies will be presented, with emphasis on pragmatic solutions to industrial vibration problems.